A new species of Neotetranychus Trägårdh (Acari, Prostigmata, Tetranychidae) from Thailand with a key to world species - Carlos H.W. Flechtmann (Persian Journal of Acarology)
Neotetranychus lek sp. nov., a spider mite collected in Thailand, is described and figured. A key to the world species of Neotetranychus, based on females, is presented.